Jerzy Grotowski and Ludwik Flaszen : five encounters with the sages - Tyszka, Juliusz (2022)
"The book contains three accounts of five public speeches and conversations with the public of two outstanding figures of theatre and performance, Jerzy Grotowski and Ludwik Flaszen, from 1993-1996. Their speeches concern their output and their current research. The content of Ludwik Flaszen's speech is very closely related to the output of Jerzy Grotowski. The accounts are written on the base of the authors detailed notes. The main subject of these narratives is their author, who quotes the speaking characters in the third person. In this way, all texts acquire a subjective character, akin to an essay, while remaining faithful to the overall message and content of the speeches and conversations cited in them. Juliusz Tyszka also uses this form of narration to describe the interpersonal context of Flaszen's and Grotowski's talks, including the content and tone of the questions asked, the reactions of listeners etc. There is also room for short, concise characteristics of these two outstanding people and their interlocutors (who are themselves sometimes also notorious). This book will be of great interest to scholars and students of theatre and performance studies and professionals in experimental theatre and performance"